Campuran Fly Ash dan Petrasoil dalam Peningkatan Daya Dukung Tanah - Indrayani -; Andi Herius; Sudarmadji -; Ahmad Mirza; Daiyan Saputra; Al Muhammad Fadil (Universitas Islam 45, 2020)
As an effort to improve the subgrade, some construction projects use petrasoil material to increase the carrying capacity of the soil, for example in the construction of the